Necrophelia and the strange case of afterlife - Sosnowska, Monika (Adam Mickiewicz University, 2013)
Drawing on Allan Edgar Poe’s provocative statement that “The death ... of a beautiful woman is, unquestionably, the most poetic topic in the world” (1951: 369), I will focus on the pivotal role of Shakespeare’s Ophelia in attesting to this assertion. Ophelia’s drowning is probably the most recognizable female death depicted by Shakespeare. Dating back to Gertrude’s “reported version” of the drowning, representations of Ophelia’s eroticized death have occupied the minds of Western artists and writers. Their necrOphelian fantasies materialized as numerous paintings, photographs and literary texts. It seems that Ophelia’s floating dead body is also at the core of postmodern thanatophiliac imagination, taking shape in the form of conventionalized representations, such as: video scenes available on YouTube, amateur photographs in bathtubs posted on photo sharing sites, reproductions and remakes of classical paintings (e.g. John Everett Millais), and contemporary art exhibitions in museums. These references will demonstrate that new cyber story – digital afterlife – is being built around the figure of Shakespearean Ophelia, unearthing the sexual attraction of the lifeless female body.
Keywords: Ophelia; popular culture; YouTube; feminist criticismv; representations of the body